Assess and rehabilitate body representations via (neuro)robotics: An emergent perspective - Risso, Gaia; Bassolino, Michela (Frontiers in Neurorobotics, 2022)
The perceptions of our own body (e.g. size and shape) does not always coincide with its real characteristics (e.g. dimension). To track the complexity of our perception, the concept of mental representations (model) of the body have been conceived. Body representations (BRs) are stored in the brain and are maintained updated through multiple sensory information. Despite being altered in different clinical conditions and being tightly linked with the self-consciousness, which is one of the most astonishing features of the human mind, the BRs and especially the underlying mechanisms and functions are still unclear. In this vein, here we suggest that (neuro)robotics can make an important contribution to the study of BRs. The first section of the work highlights the potential impact of robotics devices in investigating BRs. Far to be exhaustive, we illustrate major examples of its possible exploitation to further improve the assessment of motor, haptic and multisensory information building up the BRs. In the second section, we review the main evidence showing the contribution of neurorobotics-based (multi)sensory stimulation in reducing BRs distortions in various clinical conditions (e.g. stroke, amputees). The present work illustrates an emergent multidisciplinary perspective combining the neuroscience of BRs and (neuro)robotics to understand and modulate the perception and experience of one’s own body. We suggest that (neuro)robotics can enhance the study of BRs by improving experimental rigor and introducing new experimental conditions. Furthermore, it might pave the way for the rehabilitation of altered body perceptions.